Effects of caffeine chewing gum supplementation on exercise performance: A systematic review and meta-analysis - Barreto, G.; Loureiro, L. M. R.; Reis, C. E. G.; Saunders, B. (European Journal of Sport Science, 2023)
The aim of this systematic review with meta-analysis was to determine the effect of caffeine gum (Caff-gum) on exercise performance-related outcomes. Several databases were searched for studies assessing the effect of Caff-gum in placebo-controlled protocols involving healthy adults. Random-effects meta-analyses using standardized mean differences (SMD) were performed to determine the effect of Caff-gum on exercise outcomes with several sub-analyses (training status, exercise type, timing and dose) for potential modifying factors. 14 studies were included, totalling 200 participants. There was a significant overall effect of Caff-gum compared to placebo (SMD = 0.21, 95%CI: 0.10-0.32; p = 0.001). Subgroup analysis showed improved performance for trained (SMD = 0.23, 95%CI: 0.08-0.37; p = 0.004), but not for untrained (SMD = 0.14, 95%CI: -0.02-0.29; p = 0.07) individuals. Caff-gum improved both endurance (SMD = 0.27, 95%CI: 0.12-0.42; p = 0.002) and strength/power (SMD = 0.20, 95%CI: 0.03-0.37; p = 0.03) performance outcomes. Caff-gum was ergogenic when consumed within 15 min prior to initiating exercise (SMD = 0.27, 95%CI: 0.07-0.4; p = 0.01), but not when provided >15 min prior (SMD = -0.48, 95%CI = -1.7-0.82; p = 0.25). There was no significant effect of Caff-gum with doses <3 mg/kg body mass (BM) (SMD = 0.20, 95%CI: -0.03-0.43; p = 0.07), but there was a significant effect when the dose was =3 mg/kg BM (SMD = 0.22, 95%CI: 0.07-0.37; p = 0.01). Caff-gum supplementation may be an effective ergogenic strategy for trained athletes involved in both endurance and strength/power exercise, using a recommended dose of =3 mg/kg BM consumed within 15 min of initiating exercise.